Case report: Enhancing prognosis in severe COVID-19 through human herpes virus coinfection treatment strategies - Lu, Ye; Wang, Cuihong; Wang, Yuan; Chen, Yu; Zhao, Li; Li, Yu (Frontiers in Cellular and Infection Microbiology, 2024)
Background: In the context of increasing reports of co-infection with coronavirus disease 2019 (COVID-19), particularly with human herpes viruses (HHVs), it is important to consider the appropriate treatment options for HHVs that have been reactivated by COVID-19. Case Presentation: This study presents two cases of severe COVID-19 with HHV co-infection. The first case involved a critically ill patient with COVID-19 co-infected with herpes simplex virus type 1, confirmed using metagenomic next-generation sequencing, and another patient with severe COVID-19 experiencing Epstein-Barr virus (EBV) reactivation, as evidenced by elevated EBV-DNA levels in the serum. Treatment included high-dose glucocorticoids and sivelestat sodium, with notable improvements observed after initiating ganciclovir anti-herpesvirus therapy. Conclusion: This study underscores the significance of recognizing HHV co-infections in severe COVID-19 cases and highlights the potential of combining anti-HHV treatment, increased glucocorticoid dosages, and anti-cytokine storm therapy to enhance prognosis.